Attesting similarity: supporting the organization and study of art image collections with computer vision - Lang, Sabine; Ommer, Björn (Digital scholarship in the humanities, 2018)
Abstract. Digital possibilities and the presence of large image collections urged art history to reassess existing methods to study artworks. Big data facilita
Gesehen am 30.10.2019